Local wrinkling versus global buckling of stiff film bonded to finite-thick substrate. (May 2019) - Li, Hangfei; Cai, Shisheng; Zhang, Yingchao; Hwang, Keh-Chih; Ma, Yinji; Feng, Xue
Abstract: The serpentine interconnects that used in the stretchable electronics have periodic arc and straight segments. In the stretching process, the straight segments bonded to finite-thick substrate have global buckling and local wrinkling due to lateral contraction caused by Poisson effect. The global buckling has smaller stress level in the serpentine interconnects and can offer higher stretchability. The previously reported models to distinguish global buckling versus local wrinkling are based on wrinkling models for semi-infinite substrate. Here, an analytical model to distinguish global buckling versus local wrinkling for freestanding finite-thick substrate is established, which has general utility for future work in stretchable electronics design.